Intramolekulare Beweglichkeit und chemische Reaktivität bootförmiger Siebenringsysteme - Werner Tochtermann (CHIMIA)
10.11-dehydro-5 H-dibenzo | a. d | cycloheptenone-5 (1a, X = CO) and similar heterocyclic systems with a carboncarbon triple bond (1c, X = SO2; 1d, X = O) are useful intermediates for the synthesis of substituted di- and tribenzocycloheptenes and corresponding heterocycles. The energy parameters for the ring inversion of the boat-shaped seven-membered ring of di- and tri-benzocycloheptenes can be determined using temperature-dependent 1H-NMR-spectroscopy. Seven-membered ring systems with three anellated benzene rings show high energy barriers for conformational inversion (ΔG≠ ≥ 20 kcal/mol), so that conformational isomers or enantiomers of suitable model substances can be isolated at room temperature. In these cases the corresponding energy parameters are obtained from classical equilibration studies or from racemisation kinetics. For 1.2.3.4-tetraphenyl-9H-tribenzo | a.c.e | cycloheptenes (27) to (47) the boat conformation is completely “frozen” at room temperature (ΔG≠ ≥ 30 kcal/mol for ring inversion). Such conformational rigid compounds are thus suitable for a study of the reactivity of dia- stereotopic substituents on the tetrahedral C-9 of the system and permit predictions about the relation between conformation and reactivity among benzologous cycloheptatrienes. Remarkable differences are found in many reactions with conformational isomers of type A (quasi-equatorial C–X bond) and type B (quasi-axial C–X bond). In general the isomers B react much faster than the isomers A; these reactivity differences are discussed on the basis of model considerations. – Finally the syntheses and spectral properties of the flattened tribenzotropone-derivatives (49) and (50) are mentioned briefly.